IMF variations in unresolved stellar populations: Challenges. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Ferreras, Ignacio; La Barbera, Francesco; Vazdekis, Alexandre
Abstract: This talk focuses on the challenges facing the recent discovery of variations of the stellar initial mass function in massive early-type galaxies, with special emphasis on the constraints via gravity-sensitive spectral features.